Influence of economic factors in offer coffee of São Paulo State - Moraes, Adriano Ferreira de; Moraes-Oliveira, Adriana Ferreira de; Aparecido, Lucas Eduardo de Oliveira; Moraes, José Reinaldo Silva Cabral; Moraes, Silvia Martins de (Coffee Science - ISSN 1984-3909, 2017)
Coffee is one of the key agricultural commodities for the Brazilian economy and few studies have evaluated the influence of economic variables in the coffee supply. The objective was to evaluate the influence that economic variables promote the variation of the arabica coffee, offering on the São Paulo State Northeast. Coffee supply data and econometric variables were used in the 2000-2015 period. The variables were the total rural credit used, rural credit of agriculture, harvested coffee area, the value added in agriculture, the agriculture’s share in total value added, the coffee production value and value added tax. In modeling the coffee supply was the dependent variable and the economic variables were the independent variables, using multiple linear regression (MLR). The model developed to estimate coffee supply according to the economic variables showed a high significance (p <0.05). The evolution of coffee supply is significantly sensitive to changes in economic factors. The economic variables with the greatest influence on the coffee supply variation are the coffee harvested area and the coffee production value.